2011
DOI: 10.1111/j.1365-2869.2011.00983.x
|View full text |Cite
|
Sign up to set email alerts
|

Intact implicit probabilistic sequence learning in obstructive sleep apnea

Abstract: SUMMARYObstructive sleep apnea (OSA) belongs to the sleep-related breathing disorders and is associated with cognitive impairments in learning and memory functions. The impairments in attention-demanding cognitive functions such as working memory and executive functions are well established in OSA; however, it remains unknown if less attentiondemanding implicit sequence learning is affected. In the present study, we examined implicit sequence learning in OSA to probe the functional integrity of this fundamenta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
24
1
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 28 publications
(32 citation statements)
references
References 45 publications
6
24
1
1
Order By: Relevance
“…The exploratory study found that the sustained use of CPAP therapy increased the likelihood of an improvement in executive functioning and psychomotor speed but was not associated with a significant effect on the rate of global cognitive decline (as evaluated by the MMSE) 13. This conflict with our findings may have been due to the smaller sample size, the shorter follow-up period (13.3±5.2 months) and the less severe SAS syndrome (AHI ≥10) in the study by Cooke et al ,14 relative to the present study.…”
Section: Discussioncontrasting
confidence: 96%
See 1 more Smart Citation
“…The exploratory study found that the sustained use of CPAP therapy increased the likelihood of an improvement in executive functioning and psychomotor speed but was not associated with a significant effect on the rate of global cognitive decline (as evaluated by the MMSE) 13. This conflict with our findings may have been due to the smaller sample size, the shorter follow-up period (13.3±5.2 months) and the less severe SAS syndrome (AHI ≥10) in the study by Cooke et al ,14 relative to the present study.…”
Section: Discussioncontrasting
confidence: 96%
“…In non-demented patients, SAS is associated with impairments in attention-demanding cognitive functions attention,14 delayed long-term visual and verbal memory, visuospatial abilities and executive function, whereas language ability is unaffected 15. CPAP treatment appears to improve executive dysfunction, memory, attention and global cognitive functioning 15.…”
Section: Discussionmentioning
confidence: 99%
“…21,22 In contrast, studies that have utilized the mirror tracing task 6,15 have shown significantly flatter learning curves over practice periods, reflecting daytime practice-based learning impairments in OSA patients. However as a complex motor learning task, mirror tracing may be more susceptible to impairment in OSA populations, particularly as it relies on motor coordination and drawing, a domain that appears more substantially impaired than motor speed in OSAS.…”
Section: Discussionmentioning
confidence: 91%
“…On the basis of these research results, it is also considered necessary that general diagnosis and treatment should be provided while keeping in mind the existence of SAS as a primary method for prevention of dementia in the elderly [40][41][42]43 && ]. It was indicated that repeated apnea at night in the elderly entailed the risk of reducing cognitive functions.…”
Section: Complications and Prognosismentioning
confidence: 99%